In vitro assessment of anti-proliferative effect induced by α-mangostin from Cratoxylum arborescens on HeLa cells - El Habbash A.I.; Hashim N.M.; Ibrahim M.Y.; Yahayu M.; Elmutaal Omer F.A.; Rahman M.A.; Nordin N.; Lian G.E.C. (PeerJ Inc., 2024)
Indexed by WOS/Scopus